Explore and Evaluate the Internal Marketing Strategy of Haidilao - Zhou, Yuanyuan (2017)
In the last several decades, the relationship between internal marketing and service quality has triggered a significant attention and interest among researchers. There is an increasing number of scholars and practitioners having been aware of the importance of internal marketing. To be specific, it has been recognized that current market players are working on elevating the overall customer experiences via more motivated and creative employees. Haidilao, a very successful Chinese hot pot chain restaurant, becomes a triumphant pioneer of motivating and enabling employee through a unique internal marketing strategy. This paper will mainly focus on the rationale behind Haidilao’s success, and how different their services are compared with their competitors. Most importantly, how they capitalize on internal marketing strategy to fully enable and motivate employees, and what kind of inspirations other market players can learn from their success.